Global Health Governance: The Case of the Biopolitics of Covid-19 Vaccine Nationalism - Aditya Pratama (Global South Review, 2022)
In April 2020, the World Health Organisation (WHO), Coalition for Epidemic Preparedness Innovations (CEPI), GAVI, and the Vaccine Alliances officially launched COVID-19 Vaccines Global Access (COVAX) as a policy to facilitate equal access to COVID-19 vaccines for low-to-middle-income countries. The initiative has 184 member countries and supplies vaccines to 140 countries. By August 2021, COVAX will have provided 200 million vaccine doses instead of the 600 million doses initially proposed. The shortfall of vaccine doses through the mechanism of COVAX is not only because of production shortage but also partly due to vaccine nationalism by more high-income countries (HIC), where they secure vaccine stocks for their population. Such a phenomenon has made the Global South countries vulnerable as they have no facilities for vaccine production except India. Vaccine nationalism can be better seen from two spheres, biopolitics, and geopolitics. Previous researches on geopolitics and infectious disease are still rare. Thus, this research hopes to fill this gap. The two terms imply that vaccine nationalism involves the creation of borders and separating things and people. In other words, a particular spatial dynamic of exclusion divides the world, as manifested by an inadequate distribution of the benefits of COVID-19 vaccines between the North and the South. This research intends to analyze vaccine nationalism that causes the discrepancy in vaccine distribution between the North and the South countries from the theoretical perspectives of biopolitics and geopolitics. This research employs a case study of vaccine nationalism from 2020 to 2021. It is argued that vaccine nationalism is further divided between the North and South and the division between homeland security and world security.